Intersection traffic strategy of unmanned truck in open pit coalmines - Q X. Cai; B Y. Luan; Y Tian; X Lu; W Zhou (The Australasian Institute of Mining and Metallurgy, 2024)
The unmanned driving technology in open pit coalmines is an important technology that relies on innovation to drive the development of the open pit coal mining industry in China’s transformation of growth drivers and industrial structure upgrading. It is an important path to solve the shortage of mine truck drivers in the future mining, an important way to improve the working environment of open pit mining personnel, and an important foundation for achieving flexible production capacity in open pit mining to cooperate with the coordinated development of new energy. The communication rules at intersections are key to ensuring the safety and efficiency of unmanned driving in open pit coalmines. This paper proposes a collaborative traffic strategy between unmanned trucks for the single bucket unmanned truck intermittent process system in open pit coalmines. Based on the gap theory, this paper analyses the conflict characteristics and establishes a coordinated traffic strategy for the common intersection and merging conflicts of unmanned truck trucks in open pit coalmines, A multi-agent system simulation platform was built to evaluate the coordinated traffic efficiency under different initial average gap sizes of vehicles, with intersection traffic density, vehicle speed, and gap changes as key indicators. The results show that under the simulation conditions of this article, when the initial average gap of vehicles reaches three (four) times or more of the safe distance, the coordinated traffic performance of intersection conflicts (merging conflicts) is better, and the traffic capacity of intersections is close to the traffic capacity without conflicts.